The Kaunas Ghetto (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2004)
The history of the Kaunas Jewish community and the ghetto during the Nazi occupation may be divided into several stages: 1) the period before the establishment of the ghetto (23 June–15 August 1941); 2) the period of mass slaughter ("actions") in the ghetto (15 August–October 1941); 3) the period of stabilization (November 1941–September 1943); 4) reorganization of the ghetto as a concentration camp (October 1943 until mid–June 1944); 5) liquidation of the Kaunas ghetto (concentration camp) and imprisonment of the Jews in German concentration camps (mid-July 1944– April 1945). Discrimination and persecution of Kaunas’ Jews began in the first days of the war. When the head of German security police and SD squad, W. Stahlecker, arrived in Kaunas, the Nazis organized large-scale pogroms of Jews in Lithuania at the end of June 1941. Such pogroms were carried out in Vilijampolė where Jews were massacred by armed Lithuanian squads subordinate to German security forces (the so-called Lithuanian partisans: prisoners who had returned from the Soviet prison and criminal elements). Several thousand Jews were massacred during the pogroms, including women and children. At the beginning of July 1941, mass shootings of Jews were carried out in Kaunas’ Seventh Fort by soldiers of the Lithuanian National Work Security Battalion (TDA). About 8,000 Jews may have been massacred in Kaunas from the beginning of the war until the establishment of the ghetto on 15 August 1941. Mass slaughter continued after the establishment of the ghetto. Jews were slaughtered in the Fourth and Ninth Forts of Kaunas as well.